2019
DOI: 10.1590/s1983-41952019000300007
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis of built concrete dam

Abstract: ResumoThe conventional design of concrete gravity dams still follows the deterministic method, which does not directly quantify the effect of uncertainties on the safety of the structure. The theory of structural reliability allows the quantification of safety of these structures, from the quantification of the inherent uncertainties in resistance and loading parameters. This article illustrates application of structural reliability theory to the case study analysis of a built concrete gravity dam. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The authors observed that structural reliability provides an objective assessment of the safety of the structure or its reliability, in addition to the probability of failure. The study corroborated previous results, illustrating the lack of proportionality between the safety factors, generally adopted in the project, and the assessed probabilities of failure (Pires et al, 2019). Hu and Ma (2018) is another important reference in this theme.…”
Section: Geotechnical Measurementssupporting
confidence: 87%
See 1 more Smart Citation
“…The authors observed that structural reliability provides an objective assessment of the safety of the structure or its reliability, in addition to the probability of failure. The study corroborated previous results, illustrating the lack of proportionality between the safety factors, generally adopted in the project, and the assessed probabilities of failure (Pires et al, 2019). Hu and Ma (2018) is another important reference in this theme.…”
Section: Geotechnical Measurementssupporting
confidence: 87%
“…Jia and Chi (2015) is another important reference in this theme. Pires et al (2019) carried out a study of structural reliability analysis in a concrete gravity dam. The work showed the importance of quantifying uncertainty, both in the design phase and in the constructed dam.…”
Section: Geotechnical Measurementsmentioning
confidence: 99%
“…Routine risk and safety assessments of dams are carried out by using the determination approach (safety factor) [27], particularly in the static analysis of dams, in which the physical and mechanical properties of the dam body materials and the hydrostatic pressure are assumed to be constant values. The probabilistic analysis approach seeks to more accurately assess the behavior of dams and has been used in many studies [1][2][3][4][5]7,[9][10][11][12][13][14][15][16][17]26]. In such studies, the Probabilistic Design System (PDS) tool from ANSYS software is used to evaluate the probabilistic and reliability analysis of structures [4,6,20,24].…”
Section: Introductionmentioning
confidence: 99%
“…[1]: The COV of γC is 4 % (JCSS, 2001) and other authors have related a COV about 3 % to 5 % (Pires et al, 2019). Nominal values were based on CFBR (CFBR, 2012) and JCSS (JCSS, 2001).…”
Section: Force Moment Armmentioning
confidence: 99%
“…[5]: The COV of c´rc for all the different rocks varies from 36 % to 40 % (China Electric Council, 2000), 64 % to 69 % (Lo and Grass, 1994), 65 % (Fishman, 2009) and 44 % (Wilde and Johansson, 2013). Nominal values were based on Pires et al (Pires et al, 2019).…”
Section: Force Moment Armmentioning
confidence: 99%